Contrast enhanced CT on PET/CT imaging in clinical routine: an international survey - Annunziata, Salvatore; Testart, Nathalie; Auf der Springe, Katharina; Cuzzocrea, Marco; Nicod Lalonde, Marie; Schaefer, Niklaus; Prior, John O.; Garibotto, Valentina; Treglia, Giorgio (Frontiers in Medicine, 2023)
Aim. To perform an international survey about PET/CT imaging with contrast enhanced CT (PET/ceCT) in clinical routine worldwide.Methods. A questionnaire of ten questions was prepared for health professionals, addressing the following issues: 1) general demographic, hospital, and department information; 2) use and diffusion of PET/ceCT worldwide; 3) factors influencing the use of PET/ceCT. An invitation to the survey was sent to the corresponding authors of NM scientific articles indexed in SCOPUS in 2022 and dedicated to PET/CT imaging. Data were analysed per individual responder.Results. 191 individual responders worldwide participated in this survey. Most of the responders are using PET/ceCT in their center (74%). Interestingly, the relative use of PET/ceCT over the total PET/CT scans has an anti-gaussian distribution (<20% ceCT and >80% ceCT were most represented). Most of responders are using PET/ceCT in oncological settings (62%) and irrespectively from radiopharmaceuticals (62%). In most cases, PET/ceCT scans are reported by NM physicians alone or together by NM physicians and radiologists with an integrated report (31%).Conclusions. PET/ceCT imaging is largely used worldwide. Local factors can affect the choice of PET/ceCT in respect to conventional PET/CT imaging. Further cost-benefit analysis could be useful to consider other possible influencing variables, such as technologies, dosimetry, department organization and economics.